Population genetic structure of Hampala macrolepidota (Cyprinidae) in several populations in Malaysia using random amplified polymorphic DNA (RAPD) technique - Die, Ling Ling (Universiti Malaysia Sarawak, (UNIMAS), 2005)
This study examined thirty individuals of Hampala macrolepidota (Bleeker) using Random amplified polymorphic DNA (RAPD) -peR technique. Samples were collected from ten different locations in Malaysia. The RAPD study identified five primers useful for population analysis. 37.50% of the RAPD loci were polymorhic. Mean Nei's (1973) gene diversity was 0.1016. While, mean GST value across loci was 0.735, and the average for Nm values was 0.1798. The population's genetic distance was similar with the observed individual's pair-wise distance. The close relationship between H. macrolepidota samples was indicated by their low pair-wise genetic distance. In addition, the high percentage of sharing of banding profiles obtained also suggested that the If. macrolepidota samples from Peninsular Malaysia were closely related to the samples from Sarawak.